Why Mothers Die: An Original Research in Odisha (Medico Legal Update, 2020)
Maternal mortality is defined as the death of a woman while pregnant or within 42 days of termination ofpregnancy, irrespective of the duration and site of pregnancy, from any cause related to or aggravated bythe pregnancy or its management, but not from accidental or incidental causes. Each year in India, roughly28 million women experience pregnancy and 26 million have a live birth. Of these, an estimated 67,000maternal deaths and one million newborn deaths occur each year. In addition, millions more women andnewborns suffer pregnancy and birth related ill-health. Thus, pregnancy-related mortality and morbiditycontinues to have a huge impact on the lives of Indian women and their newborns.